Race and BMI modify associations of calcium and vitamin D intake with prostate cancer. Issue 1 (December 2017) - Batai, Ken; Murphy, Adam; Ruden, Maria; Newsome, Jennifer; Shah, Ebony; Dixon, Michael; Jacobs, Elizabeth; Hollowell, Courtney; Ahaghotu, Chiledum; Kittles, Rick
Abstract Background African Americans have disproportionately higher burden of prostate cancer compared to European Americans. However, the cause of prostate cancer disparities is still unclear. Several roles have been proposed for calcium and vitamin D in prostate cancer pathogenesis and progression, but epidemiologic studies have been conducted mainly in European descent populations. Here we investigated the association of calcium and vitamin D intake with prostate cancer in multiethnic samples. Methods A total of 1, 657 prostate cancer patients who underwent screening and healthy controls (888 African Americans, 620 European Americans, 111 Hispanic Americans, and 38 others) from Chicago, IL and Washington, D.C. were included in this study. Calcium and vitamin D intake were evaluated using food frequency questionnaire. We performed unconditional logistic regression analyses adjusting for relevant variables. Results In the pooled data set, high calcium intake was significantly associated with higher odds for aggressive prostate cancer (ORQuartile 1 vs. Quartile 4  = 1.98, 95% C.I.: 1.01–3.91), while high vitamin D intake was associated with lower odds of aggressive prostate cancer (ORQuartile 1 vs. Quartile 4  = 0.38, 95% C.I.: 0.18–0.79). In African Americans, the association between high calcium intake and aggressive prostate cancer was statistically significant (ORQuartile 1 vs. Quartile 4  = 4.28, 95% C.I.: 1.70–10.80). We also observed a strong inverse association between total vitamin D intake and prostate cancer in African Americans (ORQuartile 1 vs. Quartile 4  = 0.06, 95% C.I.: 0.02–0.54). In European Americas, we did not observe any significant associations between either calcium or vitamin D intake and prostate cancer. In analyses stratifying participants based on Body Mass Index (BMI), we observed a strong positive association between calcium and aggressive prostate cancer and a strong inverse association between vitamin D intake and aggressive prostate cancer among men with low BMI (<27.8 kg/m2 ), but not among men with high BMI (≥27.8 kg/m2 ). Interactions of race and BMI with vitamin D intake were significant (P Interaction  < 0.05). Conclusion Calcium intake was positively associated with aggressive prostate cancer, while vitamin D intake exhibited an inverse relationship. However, these associations varied by race/ethnicity and BMI. The findings from this study may help develop better prostate cancer prevention and management strategies.